2018
DOI: 10.35654/ijnhs.v1i1.2
|View full text |Cite
|
Sign up to set email alerts
|

A Social-Ecological Approach to Determine Barriers of DMSM Practice For Patients with Type 2 Diabetes Mellitus: A literature review

Abstract: Diabetes mellitus is one of the global problems the world. Since the complexity of the patient’s tasks is required in the diabetes care, the consistency to engage this various health behavior for addressing the glycemic control target is difficult to achieve. Failure management may reflect by patient, family, inadequate intervention strategies by health care provider as well as organization factor. Three databases used such as PubMed, MIDLINE, and CINAHL to address patient’s barriers, family’s barriers, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Feeling peaceful soul and mind free inflicted with the ritual is an effective treatment in dealing with the nervous tension (19). The previous study showed that the orientation on spiritual practices and selfmanagement of diabetes patients for managing (20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Feeling peaceful soul and mind free inflicted with the ritual is an effective treatment in dealing with the nervous tension (19). The previous study showed that the orientation on spiritual practices and selfmanagement of diabetes patients for managing (20)(21).…”
Section: Discussionmentioning
confidence: 99%